Frequency reconfigurable antennas for cognitive radio applications: a review - Ros Marie C Cleetus; Dr. G. Josemin Bala (Institute of Advanced Engineering and Science, 2019)
Wireless communication systems undergo tremendous growth these days and devices able to operate in a number of frequencybandsarehighlydemanded. Reconfiguration in antenna characteristic striggered the evolution of antennas that can workin multiple frequency, pattern or polarization environment.The frequency reconfigurable antennas thuse mergedarewell suited in Cognitive Radios which take part in the effective utilization of unused bands of frequencies by continuously interacting with the RF environment. Thus, Cognitive Radios enhancetheutilization of frequency spectrum and establish reliable communication. The most recent research works carried out in the arena of Frequency Reconfigurable Antennas for Cognitive Radio applications are reviewed and summed up in this paper to present the attributes and categorization. Four techniques adopted to attain frequency reconfiguration are extensively compared in this paper to find the advantages and constraints of each methodology. The applications of the works reviewed here are not only limited to Cognitive radios, but extended to a number of wireless communication services like, WLAN, WiMAX, etc